2014
DOI: 10.1186/1475-2875-13-450
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism and amino acid sequence variation in Plasmodium falciparum GLURP R2 repeat region in Assam, India, at an interval of five years

Abstract: BackgroundThe R2 repeat region of GLURP has been reported as a good genetic marker for Plasmodium falciparum genotyping. Proper knowledge of the extent and nature of P. falciparum genetic diversity using highly immunogenic R2 repeat region in malaria-endemic areas is a crucial element to understand various aspects related to immunity acquisition and disease pathogenesis.MethodsPopulation diversity of P. falciparum GLURP and amino acid sequence repeats in GLURP R2 region was studied in malaria-endemic Assam sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
15
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 38 publications
11
15
4
Order By: Relevance
“…Therefore, this 19 mer peptide of R2 region may be considered as future vaccine candidates either in the combination of other stage-specific antigens or multi-allelic vaccine of some antigens. This finding is consistent with the previous studies [ 13 , 44 ]. R2 repeat region is the immunodominant region and targeted by the human IgG antibody, which is effective in antibody-dependent cellular inhibition (ADCI).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, this 19 mer peptide of R2 region may be considered as future vaccine candidates either in the combination of other stage-specific antigens or multi-allelic vaccine of some antigens. This finding is consistent with the previous studies [ 13 , 44 ]. R2 repeat region is the immunodominant region and targeted by the human IgG antibody, which is effective in antibody-dependent cellular inhibition (ADCI).…”
Section: Discussionsupporting
confidence: 94%
“…In present study, P . falciparum msp1 , msp2 and glurp were highly diverse from central India region in respect of length as well as sequence motifs with prevalence of all the allelic families of msp1 and msp2 , which corroborates with earlier reports on Indian isolates [ 9 , 10 , 13 , 14 , 31 , 32 ]. Block-2 region of pfmsp1 exhibit repetitive tri-nucleotides and appears to be subjected to a rapid intra-genic recombination process.…”
Section: Discussionsupporting
confidence: 90%
“…The observed number of repeat sequences was less than the 12 reported recently from India. 38 The order of the amino acids in Group B was almost similar to that observed in the NCBI sequences, suggesting sequence homology to parasites from other parts of the world. The study showed some differences in the arrangements of parasite DNA sequences in the two study years, indicating possible responses of the parasite to changes in antimalarial treatment from chloroquine to ACT.…”
Section: Discussionsupporting
confidence: 64%
“…37 The high number of GLURP alleles (12 in Group A, 11 in Group B) is expected in an area of high malaria endemicity, and this is in agreement with previous reports from Asia, and most especially from Africa where 8-20 GLURP alleles have been reported. 28,38 On the contrary, in low malaria endemic countries such as Honduras, French Guyana, Brazil, and Colombia, low number of alleles ranging from two to five alleles were reported. The fact that high number of alleles were recorded in both study years in our study further corroborate that malaria transmission remains high.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, there is a trend of diagnosing a large number of alleles, which is in direct relationship between the endemicity and number of samples evaluated in case of glurp . There are few reports on the R2 repeat region of glurp from different geographical regions including India . In the present study, a total of 27 haplotypes were found when compared to the reference 3D7 sequence.…”
Section: Discussionmentioning
confidence: 52%